(untitled) (Journal of Rangpur Medical College, 2025)
Background: Bladder cancer is one of the most common cancers with non-muscle-invasive bladder cancer (NMIBC) and muscle-invasive bladder cancer (MIBC) being the two principal types. Biomarkers vimentin and Ki-67 play an important role in establishing tumor growth and potential prognostic value. Objective: The study aimed to the monitoring of Vimentin, p53, and Ki-67 expression based on histologic grade and muscle invasion in bladder urothelial carcinoma. Methods: A total of 60 bladder cancer patients, including NMIBC and MIBC patients, were being studied. Immunohistochemistry was performed to analyze the expression of vimentin and Ki-67. Statistical analysis included Pearson correlation and Chi-square tests to analyze correlations with clinicopathological parameters. Results: Widespread expression of vimentin and Ki-67 was strongly associated with increased tumor grade, lymph node status, and poor overall survival. Increased vimentin and Ki-67 expression also showed a strong association with each other, suggesting perhaps a role in tumor aggressiveness and advancement. Conclusion: The studies demonstrate that vimentin and Ki-67 are relevant biomarkers for prognosis in bladder cancer. Their expression levels may be employed for more accurate patient stratification and tailored treatment, and thus validation in larger, multi-center trials is warranted. J Rang Med Col. March 2025; Vol.10, No.1:10-15